2018
DOI: 10.1039/c8py00346g
|View full text |Cite
|
Sign up to set email alerts
|

In situ glyco-nanostructure formulation via photo-polymerization induced self-assembly

Abstract: A broad set of advanced glyco-nanostructures, rarely obtained as vesicles or never reported as wormlike micelles, is obtained using photo-initiated Polymerization-Induced Self-Assembly (Photo-PISA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 37 publications
0
83
0
1
Order By: Relevance
“…On the other hand, most of the current RAFT PISA works are still focused on the morphology diagram by modulating the species of macroinitiator/stabilizer, core‐forming block, solvent, temperature, etc. Especially, the macroinitiator/stabilizer with narrow molecular weight distribution ( M w / M n ) and defined molecular weight are always required, and the effect of M w / M n on the RAFT PISA system is rarely a concern . Previously, Armes et al compared the effect of DP of macroinitiator/stabilizer poly(lauryl methacrylate) (PLMA) chain transfer agents (CTAs) on the morphology diagram of poly(lauryl methacrylate‐benzyl methacrylate) (PLMA‐PB n MA) diblock copolymer nanoparticles, and different morphologies were actually captured in RAFT PISA system.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, most of the current RAFT PISA works are still focused on the morphology diagram by modulating the species of macroinitiator/stabilizer, core‐forming block, solvent, temperature, etc. Especially, the macroinitiator/stabilizer with narrow molecular weight distribution ( M w / M n ) and defined molecular weight are always required, and the effect of M w / M n on the RAFT PISA system is rarely a concern . Previously, Armes et al compared the effect of DP of macroinitiator/stabilizer poly(lauryl methacrylate) (PLMA) chain transfer agents (CTAs) on the morphology diagram of poly(lauryl methacrylate‐benzyl methacrylate) (PLMA‐PB n MA) diblock copolymer nanoparticles, and different morphologies were actually captured in RAFT PISA system.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we envisioned to use aqueous photo‐mediated RAFT (photo‐RAFT) polymerization that would be able to prepare well‐controlled UCST‐type copolymers directly in water at very high concentration. Although photo‐RAFT [ 28–33 ] has grasped great interests due to its versatility, rapidity, and ability to produce well‐controlled polymers, it has never been employed for the synthesis of UCST‐type polymers. This study provides new insight into UCST‐type copolymers and aims to develop facile approach to investigate such kind of thermoresponsive behavior, less described in the literature currently.…”
Section: Figurementioning
confidence: 99%
“…2‐(propylthiocarbonothioylthio)‐2‐methylpropionoic acid (TTC) (Figure 1) was used as a chain transfer agent (CTA) due to its ability to control the photo‐RAFT polymerization of acrylamide, [ 31 ] and its high stability under intense UV‐irradiation (365 nm) compared to other CTAs. [ 28,29,34 ] However, regarding its non‐solubility in water (pH = 7), a hydrophilic macromolecular chain transfer agent based on polyacrylamide (PAAm 24 ‐TTC) with very low molar mass ( M n = 1700 g mol −1 ) and low dispersity ( Đ = 1.04) was first prepared via RAFT polymerization of AAm in DMSO at 70 °C using TTC in the presence of 2,2′‐azobis(2‐methyl‐propionitrile) initiator (Figure 1; Figure S1, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…They also enhance drug bioavailability at effective doses that were previously difficult to achieve. Studies have shown that both nanoparticle geometry and size play important roles in drug delivery [ 18 , 19 ]. Nanoparticle geometry could significantly affect the rate of drug loading and drug transport, and the balance between the size and geometry is critical to the efficiency of drug delivery.…”
Section: Introductionmentioning
confidence: 99%